Techno-economic analysis and environmental impact of fuel economy labels for passenger cars in Indonesia - Silitonga, A.S.; Atabani, A.E.; Mahlia, Teuku Meurah Indra; Sebayang, A.H. (Elsevier, 2011)
In Indonesia, the transportation sector is the third largest energy consuming sector (28%) after the industrial and residential sector. Transport energy consumption is mostly driven by the road sub-sector. In order to reduce fuel consumption and emissions production in the transportation sector, fuel economy labels for passenger cars have been introduced globally. Labelling could play an important role in consumers' vehicle purchasing decisions between similar vehicles that have different fuel efficiency ratings. Currently, Indonesia does not have fuel economy labels. However, it is expected that fuel economy labels will be implemented in the near future due to the growth of passenger cars and the increasing demand for oil. This study is to calculate potential techno economic analysis and emissions reduction when implementing fuel economy labels for passenger cars in Indonesia. It has been found that fuel economy labels will save a significant amount of fuel, economical benefits and emissions reduction in this country. (C) 2011 Elsevier Ltd. All rights reserved.